1967
DOI: 10.1180/claymin.1967.007.2.04
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of α-amino-acids by copper montmorillonite

Abstract: Sorption of an acidic, amphoteric, sulphur containing and basic 7-amino-acid (glutamic acid, glycine, methionine and lysine) by copper montmorillonite was studied by chemical and X-ray methods. With glutamic acid complex formation occurs only in solution but increasing basicity of the aminoacid favours complex formation in the clay interlayers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0
1

Year Published

1971
1971
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 9 publications
1
6
0
1
Order By: Relevance
“…1a,b). As observed by Bodenheimer & Heller (1967), Cu-rich smectites show a greater affinity for glycine. In fact, Cu 2+ as a transition element is more effective in promoting an efficient coordination with the carboxylic and amino groups (Tan et al, 1999).…”
Section: Homoionic Smectite-glycine Complexessupporting
confidence: 51%
See 2 more Smart Citations
“…1a,b). As observed by Bodenheimer & Heller (1967), Cu-rich smectites show a greater affinity for glycine. In fact, Cu 2+ as a transition element is more effective in promoting an efficient coordination with the carboxylic and amino groups (Tan et al, 1999).…”
Section: Homoionic Smectite-glycine Complexessupporting
confidence: 51%
“…Factors influencing reactions between smectites and polluted solutions include the layer charge of the clay, pH, the nature and concentration of the adsorbate, temperature, and the presence of competing ions or ligands. Smectites can bind and form stable complexes with organic molecules and transition metals by a variety of mechanisms and can therefore play an important role in heavy metal cycling at the Earth's surface (Bodenheimer & Heller, 1967;Greenland et al, 1962Greenland et al, , 1965Gupta et al, 1983;Johnston, 1996). Bodenheimer & Heller (1967) suggested that in Curich smectites the ratio between the amount of aamino acid sorbed by the mineral and that in solution is inversely related to the total concentra-tion of the amino acid.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Dans ce domaine, on a pr~t6 attention ~t l'interaction d'aminoacides avec des silicates phylliteux du groupe des argiles. Ainsi en t6moignent les travaux de Talibudeen (1955), Haxaire (1956), McLaren (1958), Sieskind & Wey (1959), Sieskind (1960Sieskind ( , 1963, Greenland et al (1962Greenland et al ( , 1965, Fripiat et al (1966), et Bodenheimer & Heller (1967, orientEs vers l'explication des ph6nom~nes d'absorption et retention des mol6cules organiques dans l'espace intedamellaire.…”
Section: Introductionunclassified
“…Under alkaline conditions, the Si-O-M-O-Si bonds are more easily broken, so more O-M-(vacant site) coordination cavities are uncovered, which may accommodate the GLY molecules to form a coordination formulation, which is favorable for the loading of GLY on clay. [45][46][47] Also, the hydrogen-bonding interaction between Si-OH and the GLY molecules are contributory to the immobilization of GLY on the hydrothermally treated PAL product. 39,48 The elemental analysis of C, H, and N elements shows that the N content in GLY-PAL is 0.4%, which conrms the existence of GLY molecules in the GLY-PAL product.…”
Section: Effect Of Reaction Parameters On Adsorption Capacitiesmentioning
confidence: 99%